2014
DOI: 10.1016/j.jaapos.2014.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathy of prematurity and brain damage in the very preterm newborn

Abstract: Purpose To explain why very preterm newborns who develop retinopathy of prematurity (ROP) appear to be at increased risk of abnormalities of both brain structure and function. Methods A total of 1,085 children born at <28 weeks’ gestation had clinically indicated retinal examinations and had a developmental assessment at 2 years corrected age. Relationships between ROP categories and brain abnormalities were explored using logistic regression models with adjustment for potential confounders. Results The 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 43 publications
(43 reference statements)
1
35
0
1
Order By: Relevance
“…17 These findings suggest that there are neurologic deficits associated with ROP separate from visual acuity. In addition, Allred et al 34 found children with severe ROP were more likely to have scores on the second edition of Bayley Scales that were 2 to 3 standard deviations less than the expected mean score. They believe the preterm infant lacks growth factors, such as insulin-like growth factor 1, normally supplied by the mother in utero that protect against both retinal and brain damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 These findings suggest that there are neurologic deficits associated with ROP separate from visual acuity. In addition, Allred et al 34 found children with severe ROP were more likely to have scores on the second edition of Bayley Scales that were 2 to 3 standard deviations less than the expected mean score. They believe the preterm infant lacks growth factors, such as insulin-like growth factor 1, normally supplied by the mother in utero that protect against both retinal and brain damage.…”
Section: Discussionmentioning
confidence: 99%
“…2931 Perinatal inflammation may contribute to CNS vulnerability or injury. 3234 Alternately, cerebrovascular immaturity may play a role. 27 Cystoid macular edema within the retinal tissue may reflect cellular events that also are occurring in the CNS structures of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Presumably, many postnatal risk factors are interrelated. For example, it has been suggested that the association between ROP and brain lesions might be explained by common risk factors .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, even those children with better visual acuity had functional deficits. Allred et al12 also observed that children with a history of severe ROP scored two to three standard deviations below the mean score on Bayley Scales of Infant and Toddler Development. This finding led to the hypothesis that preterm children may have reduced growth factors, such as insulin-like growth factor 1, which is critical for both brain and retinal development and usually supplied by the mother in utero.…”
Section: Introductionmentioning
confidence: 95%